Corpus word statistics - Språkbanken Text (University of Gothenburg, 2024)
The idea is that this file should be updated regularly with new word statistics, but for technical reasons this process is currently paused.

Tanken är att denna fil ska uppdateras regelbundet med ny ordstatistik, men av tekniska skäl är denna process pausad just nu.
Ordstatistik för korpusar
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik